Automated solar tracking system using PLC - Mohamad Johan, Bakti (2009)
In our daily life, the need of energy increases each and every day. The source of electricity is commonly from motor generators that is generate from the source of coal or other element of fuel. Another new way in this era is by using solar energy. The solar energy convert solar irradiation to power that can be used in common electric appliances. Since solar is a new type of source, the usage of the solar is still small compare to the old conventional ways. The solar energy is converted when the solar cells on the solar panel detects light irradiation. However, the angle of the sun is proportional to the energy converted. If the sun is 90° vertical to the solar panel, the energy received is maximum compare to other angles. In this case, a project is developed to track the solar during the movement of the sun from morning till night. The ASTS (Automated Solar Tracking System) is developed by moving the solar panel during anytime of the day that the sun is available and the motor will move the panel to a 90° vertical angle directly to the sun. The system is controlled by OMRON Programmable Logic Controller which will process data from the sensor and convert it to output for the motor movement. As the result, a prototype of Automated Solar Tracking System is operated and able to achieve the objective of this project.